Peculiarities of psychoemotional condition of pregnant women before foetus echocardiography and parents' reaction to the prenatal diagnosis - A. Yu. Sydorenko; A. K. Kurkevych; M. V. Markova (Kazimierz Wielki University, 2015)
Sydorenko A. Yu., Kurkevych А. К., Markova М. V. Peculiarities of psychoemotional condition of pregnant women before foetus echocardiography and parents' reaction to the prenatal diagnosis = Особенности психоэмоционального состояния беременных перед эхокардиографическим  исследованием плода и реакции родителей на пренатальный диагноз. Journal of Education, Health and Sport. 2015;5(10):69-78. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.32031 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A69-78 https://pbn.nauka.gov.pl/works/654278 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.08.2015. Revised 05.09.2015. Accepted: 29.09.2015.   УДК 616.89-008-053.2+616.12-089-053.2-092   PECULIARITIES OF PSYCHOEMOTIONAL CONDITION OF PREGNANT WOMEN BEFORE FOETUS ECHOCARDIOGRAPHY AND PARENTS' REACTION TO THE PRENATAL DIAGNOSIS ОСОБЕННОСТИ ПСИХОЭМОЦИОНАЛЬНОГО СОСТОЯНИЯ БЕРЕМЕННЫХ ПЕРЕД ЭХОКАРДИОГРАФИЧЕСКИМ  ИССЛЕДОВАНИЕМ ПЛОДА И РЕАКЦИИ РОДИТЕЛЕЙ НА ПРЕНАТАЛЬНЫЙ ДИАГНОЗ   A. Yu. Sydorenko, А. К. Kurkevych, М. V.Markova А. Ю. Сидоренко, А. К. Куркевич,  М. В. Маркова   Scientific-Practical Medical Center for Pediatric Cardiology and Cardiac Surgery Kharkiv Medical Academy of Postgraduate Education   Научно-практический медицинский центр детской кардиологии и кардиохирургии МЗ Украины, Киев Харьковская медицинская академия последипломного образования МЗ Украины   Summary Currently the scientific works focus on a significant maternal and paternal psychological distress after the prenatal diagnosis. The aim of our study was to determine the volume and goals of medical and psychological help to the pregnant women suspected of congenital heart disease in the foetus. The study was conducted at the state-run Scientific and Practical Medical Children's Cardiology andCardiosurgeryCenterof the Ukrainian Health Ministry. 21 pregnant women before and after echocardiography foetus examination and 9 men were interviewed. It was found that 62% of pregnant women and 50% of husbands displayed subclinical and clinical levels of anxiety and depression before the echocardiography examination. The results highlighted that married couple who learned the prenatal congenital heart disease diagnosis need the relevant follow up program.  This program could include a consultation with the psychologist and the possible excess to enlarged database of educational materials. Key words: prenatal diagnosis, congenital heart defect, anxiety, depression, medical and psychological assistance.       Реферат Все чаще в литературе стали появляться работы посвященные значительному материнскому и отцовскому психологическому дистрессу после пренатального диагноза. Целью исследования было определение объемов и мишеней медико-психологической помощи беременным женщинам, у которых подозревается врожденный порок сердца у плода. Исследование проводилось на базе ГУ «Научно-практический медицинский центр детской кардиологии и кардиохирургии МЗ Украины». Было обследовано 21 беременную женщину до и после эхо-кардиографического исследования сердца плода и 9 мужчин (супругов). Было обнаружено, что у 62% беременных женщин и у 50% мужчин наблюдался субклинический и клинический уровень тревоги и депрессии перед эхо-кардиографическим обследованием. В статье отмечается, что супруги, получившие пренатальный диагноз ВВС у плода требует соответствующей сопроводительной программы, которая бы включала возможность консультации с психологом, а также возможность доступа к расширенной базе обучающих материалов. Ключевые слова: пренатальный диагноз, врожденный порок сердца, тревога, депрессия, медико-психологическая помощь.